Effect of Different Early Weaning Diets on Survival, Growth, and Digestive Ontogeny of Channa striatus (Bloch, 1793) Larvae - Pandi Kalaiselvan; Amit Ranjan; Mir Ishfaq Nazir; Eswaran Suresh; Albin Jemila Thangarani; Kavitha Malarvizhi (Animals)
The present study was carried out to evaluate the survival, growth, and digestive ontogeny of C. striatus larvae fed with different experimental diets from 4 days post-hatch (dph) to 32 dph at three-day intervals. A total of 24,000 larvae, with 1600 larvae per tank in triplicate and an initial mean weight of 0.64 ± 0.01 mg at 4 days post hatch (dph) were subjected to five different early weaning diets, namely Artemia nauplii (T1), co-feed diet comprising Artemia nauplii and formulated micro diet (T2), formulated micro diet (T3), formulated micro diet with protease supplementation (T4), and a commercial diet (T5). All the early weaning diets significantly affected the survival, growth, and ontogeny of the digestive system. Initially at 8 dph, C. striatus fed with T1 showed better survival and growth performance compared to other treatments. By 12 dph, the larvae fed with T1 and T2 showed similar results in terms of survival and growth performance, outperforming other treatments. However, the larvae fed with T2 and T4 outperformed T1 in survival and growth performance at 16 dph. By 24–32 dph, the larvae fed with all treatments met the basic nutritional needs for survival, with T4 fed larvae showing better growth compared to other treatments. At the end of the trial, cumulative mortality was lowest in larvae fed with T1 and highest in the larvae fed with T3 and T5. Similarly, the larvae fed with T4 showed significantly higher weight gain, specific growth rate (SGR), and average daily growth (ADG), while T1 fed larvae exhibited better feed conversion ratio (FCR) and protein efficiency ratio (PER). The enzyme activity fluctuated throughout the experimental duration. Lavae fed with T1 and T2 showed higher enzyme activities initially. However, T4 fed larvae showed higher trypsin and chymotrypsin specific activity at 16 dph along with well-developed intestinal folds with dense microvilli, higher pepsin-specific activity at 20 dph onwards with fully developed gastric glands and thicker gastric mucosal epithelium, and higher amylase and lipase activity at 16 dph with large and prominent zymogen granules in the exocrine pancreas. Peaking at 4 dph, the activity of protein metabolic enzymes (AST and ALT) sharply declined at 8 dph and increased until 32 dph. Larvae fed with T1 showed higher AST and ALT activity along with increased lipid deposits, followed by those fed with T2 and the larvae fed with T4 showing higher activity without fat accumulation but significantly lower than those fed T1 and T2. From the present research findings, it is recommended to initiate weaning for Channa striatus larvae with Artemia nauplii (from 4 dph to 8 dph) followed by a co-feeding regime (Artemia nauplii and formulated diet) between 9 and 16 dph and transition to protease-supplemented micro diet (T4) from 17 dph onwards.